Avaliação das Anomalias do Metabolismo da Glicose Após a Gravidez Complicada por Diabetes Gestacional - Matos, C (2008)
ntroduction: Gestational Diabetes Mellitus (GDM) is associated with an increased risk of maternal Diabetes Mellitus (DM). Our objective was to analyse post-partum reclassiﬁcation anomalies, and its relation with maternal history, pregnancy data and neonatal outcomes. Methods: Retrospective analysis of women with gestational diabetes between the year 2000 to 2007, aged from 16 to 45 years old; 47.2% had positive familiar history of DM and 9.1% had past history of GDM. Other maternal and gestational characteristics were collected; newborn weight and morbidity and reclassiﬁcation results were evaluated. Statistical analysis was based on descriptive methods and Spearman correlation, Kruskal-Wallis, Mann-Whitney, Qui-square and Fisher tests, and multivariate analysis by logistic regression. Results: 424 women; 69.6% underwent reclassiﬁcation; 6.1% were diagnosed impaired fasting glucose, 12.5% impaired glucose tolerance and 3.7% DM. A relation was established, between progression to impaired glucose metabolism and family history of diabetes, elevated BMI before pregnancy, earlier gestational age at diagnosis and need for insulin therapy. Discussion: Only elevated BMI before pregnancy seems to predict progression to altered glucose metabolism. Therefore, it is important to develop preventive strategies for obesity and be aware that every woman with GDM undergoes reclassiﬁcation tests.